Product Strategies and Advertising in Small Firms: A Study of Punjab Units - Gautam, Raj Kumar (Indian Journal of Marketing, 2012)
The product provides primary value to a customer. A Product is the currency which ultimately gets exchanged because a customer wants the product, and the company wants cash from the customer to continue business efforts. The selection of a product for manufacturing is being made on the basis of age-old factors and in the absence of marketing research (Kumar, 1991). Starting with the manufacturing strategy, more attention is required in the way in which product quality, process flexibility, delivery dependability and manufacturing cost influence the firm's foreign business (Meijboom and Bart, 1997). The customer pays more attention to the company due to a product and features of the product. In the era of competition, markets are flooded with product variety and range, which leads to stiff competition. The small industry is also facing competition directly or indirectly from all sizes of national and international organizations. Hence, it is very important to produce and serve the market with quality products with differentiation. Modern product manufacturing strategies are highly essential in the present time. An important element of product strategy is new-product development with new-product range and product line.